Digital Actors and Digital Platforms in the System of International Relations: Between Complex Interdependence and Online Sovereignty - P. S. Kanevskiy; K. Y. Petrov (Международная аналитика)
The article analyzes deep changes in international relations that are taking place in the context of the increasing role of digital actors and platforms in shaping the global agenda. The emergence of the Internet was a turning point in the development of the entire system of global communications. The Internet changed the way information is spread and public opinion is shaped, while digital platforms became a new factor of globalization. At the same time, as the authors demonstrate, the original nature of the Internet, which was viewed by the United States and the West as an integral part and technology of the liberal order, in the end started to reflect the increasing confrontation between states, and became a space for the spread of political conflicts, stereotypes and information wars. In addition, new digital oligopolies began to shape the digital space based on their corporate interests, prioritizing their market share rather than the quality of online discussions and the strengthening of the civic democratic culture. The weaponization and securitization of the Internet is a logical continuation of the crisis of the global liberal order. The complex interdependence, which was strengthened by digital actors and digital platforms, is increasingly being replaced by the idea of digital sovereignty. States aim to decouple from a single communicative space and to create norms protecting them and their citizens from the excessive influence of the Big Tech. The authors conclude that we are experiencing the sunset of the era of information openness. Depoliticization of the Internet is impossible without reducing international tension and reviving the spirit of rationalism in world politics. Only through getting back to reason can we return to the Internet the role of a creative, rather than destructive technology.